An upper limit to the secular variation of the gravitational constant from white dwarf stars - García Berro, Enrique (2011)
A variation of the gravitational constant over cosmological ages modifies the main sequence lifetimes and white dwarf cooling ages. Using an state-of-the-art stellar evolutionary code we compute the effects of a secularly varying G on the main sequence ages and, employing white dwarf cooling ages computed taking into account the effects of a running G, we place constraints on the rate of variation of Newton's constant. This is done using the white dwarf luminosity function and the distance of the well studied open Galactic cluster NGC 6791. We derive an upper bound Ġ/G ~ −1.8 × 10−12 yr−1. This upper limit for the secular variation of the gravitational constant compares favorably with those obtained using other stellar evolutionary properties, and can be easily improved if deep images of the cluster allow to obtain an improved white dwarf luminosity function.